2021
DOI: 10.1039/d1cc00460c
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and synthesis of hollow Fe–N/C electrocatalysts for enhanced oxygen reduction reaction

Abstract: Molecular design to validation of relevant Fe–O bonds, performance tests and characterization results demonstrate that an FeN2+2–O coupled hollow carbon structure as an active site can exhibits superior cell performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Therefore, electrons on the CoO were partially transferred to Fe 3 O 4 because the Fe 3 + electronegativity is stronger than that of Co 2 + , which resulted in charge redistribution (i. e., the Co 2 + peaks of Fe 3 O 4 / CoO@NC were red-shifted compared with the single CoO). The Fe 2p 3/2 spectra of Fe 3 O 4 /CoO@NC-750 (Figure 5(f)) can be divided into two peaks at 710.5 (Fe 2 + species) and 712.9 eV (Fe 3 + species) [29,56]. The Fe 2p 1/2 spectra showed a peak at 723.9 eV (Fe 2 + species) and 726.2 (Fe 3 + species) [51,57].…”
Section: Xpsmentioning
confidence: 98%
“…Therefore, electrons on the CoO were partially transferred to Fe 3 O 4 because the Fe 3 + electronegativity is stronger than that of Co 2 + , which resulted in charge redistribution (i. e., the Co 2 + peaks of Fe 3 O 4 / CoO@NC were red-shifted compared with the single CoO). The Fe 2p 3/2 spectra of Fe 3 O 4 /CoO@NC-750 (Figure 5(f)) can be divided into two peaks at 710.5 (Fe 2 + species) and 712.9 eV (Fe 3 + species) [29,56]. The Fe 2p 1/2 spectra showed a peak at 723.9 eV (Fe 2 + species) and 726.2 (Fe 3 + species) [51,57].…”
Section: Xpsmentioning
confidence: 98%
“…It is widely reported that Fe−N−C can effectively reduce the ORR overpotential, improve the reaction kinetics, and increase the ORR activity [9] . So, Fe−N−C is also an excellent electrocatalytic material suitable for MFC cathode [10] …”
Section: Introductionmentioning
confidence: 99%
“…[9] So, FeÀ NÀ C is also an excellent electrocatalytic material suitable for MFC cathode. [10] In the single-chamber MFC, the cathode driving the ORR and the anode to which the bacteria attach are in the same electrolyte environment due to the absence of proton exchange membrane isolation. After the long-term operation, the bacteria on the MFC anode will spread to the cathode, and a biofilm will gradually adhere to the cathode surface, causing biological contamination.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, several concepts and precursors have been utilized to develop many advanced non-precious metal catalysts that show enhanced activity towards the electrochemical reduction of oxygen in both alkaline and acidic media. These materials include metal-organic frameworks [19][20][21][22], conductive-polymer-based complexes (pyrolyzed and non-pyrolyzed) [23,24], non-pyrolyzed transition metal macrocycles [25,26], materials based on metal oxides/carbides/nitrides [27,28], and heat-treated and untreated metal-nitrogen-carbon catalysts [29][30][31]. Recently, a curious approach emerged regarding transition metal-nitrogen-carbon electrocatalytic materials derived from the thermal decomposition of hexacyanometallates, where a carbon-nitrogen-based matrix coordinates metal centers [16,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%